Analisis Pengaruh Harga, Kualitas Produk dan Promosi Terhadap Keputusan Pembelian pada Produk Minuman Deles di Desa Kalibaru Kulon, Kecamatan Kalibaru Kabupaten Banyuwangi - Faizal Riedho Putra Soesanto; Nursaidah Nursaidah; Putri, Tatit Diansari Reski (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
Business competition in the contemporary beverage industry is increasingly competitive, prompting companies to design the right marketing strategy to attract consumers. One of the strategic steps that is often taken includes setting appropriate prices, continuously improving product quality, and implementing creative and effective promotions. However, in the case of Deles Drinks in Kalibaru Kulon Village, Kalibaru District, Banyuwangi Regency, there is a phenomenon of declining sales which indicates that there is a problem in the implementation of the marketing strategy. Therefore, an in-depth evaluation is needed regarding the influence of price, product quality, and promotion on consumer purchase decisions. This study aims to analyze the extent to which price, product quality, and promotion can influence the purchase decision of Deles Drink. The study uses a quantitative method with a causality approach, in which the cause-and-effect relationship between independent variables (price, product quality, and promotion) and bound variables (purchase decisions) is analyzed in depth. Data was collected through the distribution of questionnaires to 100 respondents selected by purposive sampling technique, which is the selection of respondents based on certain criteria relevant to the research. In data processing, this study used multiple linear regression analysis with the help of SPSS software. The results of the analysis show that price, product quality, and promotions have a positive and significant influence on purchase decisions. These findings reinforce the assumption that consumers will be more interested in making purchases if the prices offered are competitive, the quality of the product is as expected, and the promotions carried out are effective in attracting attention. Therefore, the management of Deles Beverages needs to strengthen these three aspects to increase competitiveness and expand market share. This research also makes practical contributions for business actors in the contemporary beverage industry, especially in understanding the importance of integrating pricing strategies, product quality, and promotion to increase consumer loyalty and purchase decisions.